Parental responsibility and the application of regulated forum non conveniens of article 15 of Council Regulation (EC) Nº 2001/2003 : the ECJ judgement of 27th October 2016 - Sánchez López, Bárbara (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
This ECJ judgment addresses the scope of application and the conditions that art. 15 of Council Regulation (EC) nº 2201/2003 (…) impose in order to a court having jurisdiction may transfer the case to a court of another Member State which the child has a particular connection with and it would be a court better placed to hear the case taking into account the best interest of the child. The Judgment examines the circumstances of this particular and regulated forum non conveniens that is characteristic of this Council Regulation.